Sesbania Grandiflora - Bhat, A. S.; Menon, M. M.; Soundararajan, T. N.; Bhargava, R. L. (Indian Forester, 1971)
As compared with most of the pulpwoods at present being grpwn extensively, Sesbania Grandijlora appears to be capable of producing at a very short rotation, a much higher cellulosic raw material per unit area of plantation, as evident from the study of locally grown stands and from the pilot introduction trial conducted with this species.The wood has been tested and has been found to be extremely good for semi-chemical pulping, which can be used as a furnish for cheap printing, writing, magazine and news printing papers. The proportions of such a pulp will be in the range of 40-60 per cent admixed with chemical pulp from bamboo. The observations regarding its growth and pulping characteristics noted have prompted under-taking further field trials with this species on an extensive scale.